Identification and deletion of duplicate subtrees in classification tree for test case reduction. (1st January 2013) - Prema, P.; Ramadoss, B.; Balasundaram, S.R.
Among the many widely used specification-based testing techniques, classification tree method (CTM) is one of the most acclaimed methods, to generate test cases from the functional specification. While integrating applications, there may be a possibility for the occurrence of duplicates, which affects the performance improvement of integrated applications (IAs). To test such applications, CTM can be used to generate test cases. A classification tree, thus generated for this application may have duplicate subtrees and test cases generated from this classification tree may also have redundant test cases. Thus, the existence of duplicate subtrees affects the quality and effectiveness of the classification tree. This paper concentrates on identifying duplicate subtrees through searching techniques and also proposed an enhanced duplicate terminal subtree deletion algorithm, which helps to reduce the number of redundant test cases. Finally, this paper compares the proposed algorithm with the existing one using case studies.